Injúria renal aguda em cadelas com piometra: a importância do diagnóstico precoce - Ribeiro, Luana de Sousa (2019)
Acute renal injury (ARF) causes the prognosis of female dogs with pyometra to be reserved, with a greater probability of death. The diagnosis of this complication is a challenge for the veterinarian because the disease is clinically silent. In this sense, the use of laboratory and ultrasonographic exams helps to detect the initial phase of the disease. Therefore, this article had the objective to evaluate the symmetrical dimethylarginine (SDMA) as an early biomarker in an acute kidney cells injury in female dogs with pyometra. To do this, nine animals with pyometra without renal azotemia, but with diagnosed acute renal insufficiency (ARI) by the resistivity (RI) and pulsability (PI) indexes in color Doppler and pulse modes, where compared to 10 healthy animals submitted to elective ovarianhisterectomie (OSH). The results were compared with other laboratory indicators of impairment of the kidneys in non-azotemic renal animals. It is concluded from the data obtained that the relation protein/urinary creatinine (RPCU) is more precocious than SDMA, which makes it the laboratory analysis of choice for the detection of ARI in dogs with pyometra.